The Influence of Digital Communication Strategies on Consumer Purchase Intention Among SMEs on Instagram - R. Aj Rizqia Anisa Putri; Muhammad Doni Al Rafly Tanjung; Rio Kurniawan (Literasi Nusantara, 2026)
The rapid growth of digital technology has transformed business communication practices, particularly among Small and Medium Enterprises (SMEs) utilizing social media platforms such as Instagram. This study aims to examine the influence of digital communication strategies on consumer purchase intention among SMEs operating on Instagram. Using a qualitative descriptive approach through a literature review method, this study analyzes previous research, academic literature, and digital marketing practices related to communication strategies, consumer behavior, and social media marketing. The findings indicate that effective digital communication strategies, including attractive visual content, persuasive messaging, audience engagement, content consistency, and interactive communication, significantly contribute to increasing consumer purchase intention. Instagram features such as Stories, Reels, Live Streaming, and Direct Messages provide opportunities for SMEs to establish stronger relationships with consumers and enhance brand awareness. Furthermore, the application of the AIDA model and persuasion theory demonstrates how communication strategies can influence consumer decision-making processes from attention to purchasing action. The study concludes that digital communication strategies play a crucial role in influencing consumer attitudes, strengthening trust, and encouraging purchase intentions in digital business environments. The findings provide practical insights for SMEs seeking to optimize communication effectiveness and improve marketing performance through social media platforms.